Expression of p53 Mutants in Determining the Degree of Differentiation and Prognosis of Colorectal Adenocarcinoma in the Laboratory of Anatomical Pathology of Haji Adam Malik Hospital Medan - Dewi, Yessi Devita Azraini (CV. Devitara, 2024)
Cancer is important problem in public health worldwide especially in developed countries. About 10 millions new cases was diagnosed every year. Colorectal carcinoma is more common in man than woman. Despite significant advances in both surgical methodology and adjuvant therapy regimes, long-term survival for CRC patients remains in the range of 50-60%. Based on WHO, 90 % colorectal carcinoma was adenocarcinoma. Colorectal carcinoma is caused by a collection of various genetic changes and the most common cause is a loss of function of the p53 tumor suppressor gene. P53 tumor suppressor gene plays an important role in cell cycle and apoptosis. This gene encodes for a 53 kDa phosphoprotein and is frequently targeted for inactivation in a wide range of tumours. It is the target of point mutations and small deletions and insertions that lead to total or partial abolition of protein function. Inactivation is believed to abolish the ability of p53 to maintain genomic integrity through regulation of various activities, including the control of cell cycle arrest, DNA repair and apoptosis. Accumulation of p53 in tumor cells can be detected with a specific p53 antibody. Mutation on p53 gen and overekspression of p53 is common incolorectal carcinoma tissue then p53 mutant and p53 wild type can be targeted by p53 specific antibody. P53 overexpression associated with colorectal carcinoma histologycal grade and tend more common in colorectal carcinoma with high proliferation activity. To assess p53 mutan expression in determining differentiation grade and prognose adenocarcinoma colorectal and the prognose of adenocarcinoma colorectal at Anatomic Pathology laboratory of RSUP Haji Adam Malik Medan. The study design was observational design with cross sectional approach. All variables were immunohistochemically stained with p53 mutant. The variables were measured only once and at one moment. The samples used in this study were the sample preparation of paraffin blocks from 59 colorectal carcinoma tissues which diagnosed patologically according inclusion criteria. All variables were immunohistochemically stained with p53 mutant. Distribution of patients by age group mostly aged over 60 years which is 24 cases (40.68%). Distribution of patients by sex mostly male which is 36 cases (61.02%). 36 cases (61,02%) were located on colon. The majority, 27 cases (45,76%) were diagnosed as well differentiated adenocarcinoma. Colorectal carcinoma samples based on p53 mutant expression were score +1 (weak) were 35 cases (59,32%). Calculation of chi-square with 2x2 crosstab table, p value = 0.427 (p value> 0.05). No difference between p53 mutant expression with histopathological grade in colorectal adenocarcinoma.